Creating and managing a database of clinical stories for ethical analysis: moral and legal issues - Furlan, Enrico; Tusino, Silvia; Piva, Laura (Medicina e Morale, 2025)
The ethical analysis of clinical stories is generally regarded as a crucial tool in the bioethics training of healthcare professionals. For this reason, the research group “Moral Philosophy and Bioethics” at the University of Padua systematically incorporates it in their educational activities. Over the years, the group has collected narratives from numerous healthcare professionals and developed dozens of clinical stories that present significant ethical dilemmas. This led to the idea of creating a database of such stories, along with a reflection on the ethical and legal issues associated with this initiative.